Designing an Interface for the Garut Police Satbinmas Activity Information System Based on User Centered Design - Khaerani, Aghisti; Budiman, Tedi (Jurnal Accounting Information System (AIMS), 2026)
The development of information technology encourages public agencies to improve the quality of services through the use of more effective digital systems. In the police environment, particularly the Community Development Unit (Satbinmas) of the Garut Police, the process of managing and reporting activities is still carried out semi-manually using Google Spreadsheets, potentially causing data duplication and hindering the recapitulation and monitoring of activities. This condition indicates the need for an information system supported by a user interface that suits the needs of field users. This study aims to design a web-based user interface for the Satbinmas Activity Management Information System of the Garut Police by applying the User-Centered Design (UCD) approach. The research method was carried out iteratively through the stages of observation, user interviews, interface design, and usability evaluation using the System Usability Scale (SUS) involving five Satbinmas personnel. The evaluation results showed an average SUS value of 78.5 which is included in the good category, indicating that the developed interface has an adequate level of usability and is acceptable to users. This study concludes that the application of UCD is able to produce an interface design that supports the efficiency and accuracy of Satbinmas activity management, and provides a contribution in the form of a reference for the development of information system interfaces based on user needs in the regional police environment.